1999
DOI: 10.3354/meps179285
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton nutrient control in the oligotrophic South Pacific subtropical gyre (Tuamotu Archipelago)

Abstract: The identification of the nutrients likely to limit phytoplankton in the Tuamotu Archipelago ocean (South Pacific subtropical gyre) is deduced from DIN (NO3-+ NOz-+ NH,'), PO,", and SiOz in situ concentrations and strengthened by the results of 4 other studies on the same area:(1) 0,,,, the maximum quantum yield of photosynthesis, (2) phytoplankton cell size, (3) nutrient enrichment on natural populations, (4) bacterial biomass and nutrient limitation of bacteria. The low D,,,, and the small s~z e of phytoplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…It has been suggested that open ocean algae may have adapted to low nutrient conditions by losing their ability to grow fast (Jackson, 1980). However, Brand and Guillard (1981) demonstrated that several species of microalgae isolated from oligotrophic waters have the same growth potential as those cultured in the laboratory, and numerous studies in the central gyres have found growth responses of phytoplankton to experimental nutrient additions (Eppley et al, 1973;DiTullio et al, 1993;Graziano et al, 1996;Dufour et al, 1999). During the AMT cruises, we found dramatic increases in productivity and growth in some areas (e.g.…”
Section: Phytoplankton Growth In the Oligotrophic Regionsmentioning
confidence: 75%
“…It has been suggested that open ocean algae may have adapted to low nutrient conditions by losing their ability to grow fast (Jackson, 1980). However, Brand and Guillard (1981) demonstrated that several species of microalgae isolated from oligotrophic waters have the same growth potential as those cultured in the laboratory, and numerous studies in the central gyres have found growth responses of phytoplankton to experimental nutrient additions (Eppley et al, 1973;DiTullio et al, 1993;Graziano et al, 1996;Dufour et al, 1999). During the AMT cruises, we found dramatic increases in productivity and growth in some areas (e.g.…”
Section: Phytoplankton Growth In the Oligotrophic Regionsmentioning
confidence: 75%
“…On the other hand, nutrient budget analysis between lagoon and open ocean evidenced that oceanic waters are not an important N source for the lagoon. Surface oceanic water around Tuamotu atolls typically has average nutrient concentrations of 0.02 lM DIN and 0.21 lM SRP (Dufour et al, 1999). However, higher DIN values at the OCE station in October 2010, especially at 50 m (0.23 lM), indicates a possible surface N-enrichment due to turbulent vertical mixing of the waters along the shelf break, as observed in Tikehau atoll (Charpy-Roubaud et al, 1990).…”
Section: Environmental Conditions and Nutrient Statusmentioning
confidence: 88%
“…Average silicate concentration in Ahe (1.55 ± 0.05 lM) was relatively low but slightly higher than average silicate concentration in other Tuamotu atolls (1.0 ± 0.1 lM; Dufour et al, 1999).…”
Section: Environmental Conditions and Nutrient Statusmentioning
confidence: 89%
See 1 more Smart Citation
“…1). The small size of prokaryotes has been inferred to provide a competitive advantage under these nutrientlimited conditions (Dufour et al 1999). …”
Section: Introductionmentioning
confidence: 99%